PENGENALAN DASAR PEMROGRAMAN MENGGUNAKAN WEBSITE CODECOMBAT UNTUK MENINGKATKAN LITERASI DIGITAL - Feronata Kholda Sahillah; Nadhifah Azzahra Putri; Afrikhna Aqilatul Hamidah; Unna Alifa Askya; Maylinda Eka Saputri; Darso (Abdi Jurnal Publikasi, 2026)
The rapid development of information technology requires every generation to have digital literacy skills from an early age. This community service activity aims to introduce basic programming to children using the CodeCombat website to improve their digital literacy. The activity was conducted at SD Negeri 1 Banteran, Banyumas, involving 28 students from grades 4. The method used was Action Research, dividing the activity into four sessions: unplugged activity, guided exploration, creative challenges, and reflection. The evaluation was carried out using pre-tests, post-tests, and Likert scale observation sheets. The results showed a significant increase in students' understanding of basic programming concepts, with an average increase of 45.75%. The highest improvement was seen in writing basic syntax (47%), understanding sequential concepts (46%), and simple debugging skills (44%). Furthermore, students' motivation and enthusiasm for learning coding increased by 46%. It is concluded that the gamification approach using CodeCombat is highly effective in introducing computational thinking and improving digital literacy among elementary school students.